2014
DOI: 10.1159/000355083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Legislation on Passive Smoking in Spain

Abstract: Background: In 2005, the Spanish government approved Law 28/2005 on health measures against smoking; this was amended in 2010 by Law 42/2010. Objective: The purpose of this study was to assess the impact of these laws on passive smoking. Methods: Three epidemiological studies were conducted on a representative sample of the population via telephone surveys. The first was conducted prior to the first law coming into force, the second a year after its approval and the third a year after the approval of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
3
5
0
Order By: Relevance
“…Furthermore, there is scarce evidence about the impact of the smoking laws on the prevalence of smoking [10]. Our results are in line with those of a similar study carried out in Spain in the general population in a similar period [11], but a slight decrease in prevalence was observed among Spanish workers [12]. The increase in the prevalence of tobacco consumption in the oldest groups is not a coincidence and reflects changes occurring in tobacco consumption in Spain, where women were mainly non-smokers until the 1980s.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there is scarce evidence about the impact of the smoking laws on the prevalence of smoking [10]. Our results are in line with those of a similar study carried out in Spain in the general population in a similar period [11], but a slight decrease in prevalence was observed among Spanish workers [12]. The increase in the prevalence of tobacco consumption in the oldest groups is not a coincidence and reflects changes occurring in tobacco consumption in Spain, where women were mainly non-smokers until the 1980s.…”
Section: Discussionsupporting
confidence: 91%
“…It found that the rate of tobacco use among the physicians at these hospitals was 52.2% [12]. It may be deduced by comparing the data from our study to the data from a study by Reyes Urueña et al [8] that a reduction in the prevalence of tobacco use among Spanish health professionals started to become evident from the time the Spanish legislation regulating tobacco use was implemented [9,10,13]. …”
Section: Discussionsupporting
confidence: 53%
“…Moreover, another longitudinal study, showed a significant decrease in the prevalence of selfdeclared SHS exposure at workplaces, during leisure time, at home, and public transport after the application of the two Spanish smoking legislations 25 . Other studies, carried out in Spain using questionnaire, showed a decrease in self-declared SHS exposure in all the studied settings after the application of the smoking legislations 16,26,27 . Similar results can be found in Ireland 28 , Scotland 29 , Italy 30 , and USA 31 .…”
Section: Discussionmentioning
confidence: 61%